Transposon mediated functional genomic screening for BRAF inhibitor resistance reveals convergent Hippo and MAPK pathway activation events - Li Chen; Iulian Pruteanu-Malinici; Anahita Dastur; Xunqin Yin; Dennie Frederick; Ruslan I. Sadreyev; Cyril H. Benes (Scientific Reports)
Abstract Genotype-informed anticancer therapies such as BRAF inhibitors can show remarkable clinical efficacy in BRAF-mutant melanoma; however, drug resistance poses a major hurdle to successful cancer treatment. Many resistance events to targeted therapies have been identified, suggesting a complex path to improve therapeutics. Here, we showed the utility of a piggyBac transposon activation mutagenesis screen for the efficient identification of genes that are resistant to BRAF inhibition in melanoma. Although several forward genetic screens performed in the same context have identified a broad range of resistance genes that poorly overlap, an integrative analysis revealed a much smaller functional diversity of resistance mechanisms, including reactivation of the MAPK pathway, PI3K-AKT pathway, and Hippo pathway, suggesting that a relatively small number of therapeutic strategies might overcome resistance manifested by a large gene set. Moreover, we illustrated the pivotal role of the Hippo pathway effector TAZ (encoded by the WWTR1 gene) in mediating BRAF inhibition resistance through transcriptional regulation of receptor tyrosine kinases and through interactions with the E3 ubiquitin ligase NEDD4L.